First record of Psittacara erythrogenys (Psittacidae) in Colombia - Eliana Fierro-Calderón; Karolina Fierro-Calderón (Caldasia)
The red-masked parakeet Psittacara erythrogenys was originally distributed in the forests of Ecuador and northwestern Peru, mainly below 1500 m of elevation. Due to pet trade, this parakeet has current stable breeding populations in the United States, Spain, Chile, and Puerto Rico. We describe the first record of the species in Colombia in March 2018, as well as other observations from the city of Santiago de Cali.